EVALUATION OF RELATIVE AMPLITUDE ON SYNTHETIC SEISMIC MARINE 2D - AFIFAH AMATULLAH (NIM : 123 07 062), BILQIS
The objectives of this study are to find out how to get a preserved amplitudes, and to evaluate the preservation of amplitudes. On seismic data, the propagation of wave is affected by spherical divergence, diffraction, or coherent noise that causing the amplitude becomes non-preserved. By applying amplitude correction, data is compensated and at last produce a preserved data. True Amplitude Recovery (TAR) is a decay amplitude correction due to spherical divergence. However, coherent noise suppression by F-K filter and random noise suppression by F-X deconvolution should also be done to generate data that has a high signal-noise ratio. Two workflows was done in this study, i.e. applying TAR-F-X deconvolution-F-K filter and applying TAR-F-K filter-F-X deconvolution, so we can find out wether coherent noise suppression or random noise suppression first to be done. As a result, each process produced relatively different amplitudes. Similarity trend of Amplitude Variation with Angle (AVA) curve and distribution of intercept-gradient on synthetic seismic marine 2D with calculation of Aki-Richard showed that data has preserved. In this study, applied TAR (with 1/dist correction), F-X deconvolution (with 10-tras horizontal window, 500ms vertical window, and 8-75 Hz frequency range), then applied F-K filter could produce a preserved data.